Correction: Chemoselective dehydrogenative esterification of aldehydes and alcohols with a dimeric rhodium(ii) catalyst. Issue 9 (28th July 2017) - Cheng, Junjie; Zhu, Meijuan; Wang, Chao; Li, Junjun; Jiang, Xue; Wei, Yawen; Tang, Weijun; Xue, Dong; Xiao, Jianliang
Abstract : Correction for 'Chemoselective dehydrogenative esterification of aldehydes and alcohols with a dimeric rhodium(ii ) catalyst' by Junjie Cheng et al., Chem. Sci., 2016, 7, 4428–4434.